The Effects of Meal Timing and Frequency, Caloric Restriction, and Fasting on Cardiovascular Health: an Overview - Andrea Maugeri; Manlio Vinciguerra (The Korean Society of Lipid and Atherosclerosis, 2020)
Cardiovascular disease (CVD), which is the leading cause of death worldwide, is strongly affected by diet. Diet can affect CVD directly by modulating the composition of vascular plaques, and indirectly by affecting the rate of aging. This review summarizes research on the relationships of fasting, meal timing, and meal frequency with CVD incidence and progression. Relevant basic research studies, epidemiological studies, and clinical studies are highlighted. In particular, we discuss both intermittent and periodic fasting interventions with the potential to prevent and treat CVD.